Developing a Structural Model of Academic Engagement Based on Academic Self-Regulation and Academic Buoyancy: The Mediating Role of Epistemological Beliefs in Students - Bayyenat, Bahare; Akbari, Hamze; Shariatnia, Kazem (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to develop and test a structural model of academic engagement based on academic self-regulation and academic buoyancy, with the mediating role of epistemological beliefs among secondary school students.Methods and Materials: This applied study used a quantitative, descriptive-correlational design based on structural equation modeling. The statistical population included all male students enrolled in the second period of high school in Gorgan, Iran, during the 2024–25 academic year. A sample of 350 students was selected through multistage cluster random sampling. Data were collected using the Academic Engagement Questionnaire, Academic Self-Regulation Questionnaire, Academic Buoyancy Scale, and Schommer Epistemological Beliefs Questionnaire. The data were analyzed using Pearson correlation coefficients and structural equation modeling through SPSS and AMOS.Findings: The results showed that academic self-regulation had a positive and significant direct effect on academic engagement (β = .67, p = .001). Academic buoyancy also had a significant direct effect on academic engagement (β = .27, p = .001). In addition, epistemological beliefs significantly predicted academic engagement (β = .14, p = .001). The indirect effect of academic self-regulation on academic engagement through epistemological beliefs was significant (β = .69, p = .001). Moreover, the indirect effect of academic buoyancy on academic engagement through epistemological beliefs was significant (β = .56, p = .001). The model showed acceptable fit indices, including CMIN/DF = 1.32, RMSEA = .07, SRMR = .03, CFI = .92, GFI = .91, and NFI = .98.Conclusion: Overall, the model explained 64% of the variance in academic engagement. These findings highlight the importance of self-regulated learning, academic buoyancy, and epistemological beliefs in promoting students’ academic engagement.